The NCL Natural Constraint Language - Zhou, Jianyang (Springer Berlin / Heidelberg, 2012)
This book presents the Natural Constraint Language (NCL) language, a description language in conventional mathematical logic for modeling and solving constraint satisfaction problems. It uses illustrations and tutorials to detail NCL and its applications.